Experimental investigation of the flexural ductility of singly reinforced concrete beam using normal and high strength concrete - Atur P.N. Siregar (Journal of Sustainable Engineering: Proceedings Series, 2019)
This paper discusses and reports based on the experimental investigation of the flexural ductility of singly reinforced normal strength and high strength concrete beams. Compressive concrete strength of 40 and 95 MPa were employed to create singly reinforced normal strength and high strength concrete beams, respectively. Fourteen samples made of normal and high strength concrete were engaged to observe the flexural ductility behaviour of beams on the basis of four point bend testing. Analysis on the basis of the flexural cracking, ultimate failure and curvature ductility were carried out to derive the comparison of singly reinforced normal strength and high strength beams. The beams using high strength concrete revealed a higher ductility ratio than that of normal strength concrete, i.e. 4.50 for high strength concrete and 2.60 for normal strength concrete.